Pengaruh Keamanan, Kepuasan, Kemudahan dan Kepercayaan terhadap Loyalitas Pengguna BSI Net Banking di Bank Syariah Indonesia KCP Suropaticore Bandung - Fitria Mella Adestyan; Ida Rapida (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
The background of the research is the fluctuating number of customers using BSI Net Banking at BSI KCP Suropaticore in the last five years. This prompted the authors to examine the aspects of security, satisfaction, convenience and trust associated with loyalty of BSI Net Banking users at BSI KCP Suropaticore. Associative quantitative research type, primary data obtained through questionnaires and secondary data through observation, interviews, and literature study. The population of 673 using the Slovin formula obtained a sample of 87 people. Data analysis used SPSS 25 for validity test, reliability test, data normalization test, correlation and regression analysis, coefficient of determination analysis, t test, and F test. The results partially show that the variables of security, satisfaction, convenience, and trust have a significant effect on loyalty. Simultaneously these four variables also significantly influence loyalty.